PENGARUH GREEN INTELLECTUAL CAPITAL DAN KOMPETENSI KEWIRAUSAHAAN AKUNTANSI TERHADAP SUSTAINABLE PERFORMANCE UMKM DI KABUPATEN KARAWANG - Sintia Ayuandira Rahayu; Dedi Mulyadi; Yanti Yanti (ITB AAS Indonesia Surakarta, 2024)
This study aims to evaluate and examine the effect of green intellectual capital and accounting entrepreneurial competency on sustainable performance of micro, small and medium enterprises (MSMEs) in Karawang regency. This study uses a quantitative methodology with primary data collection. The population of this study consisted of micro, small and medium enterprises (MSMEs). The number of samples in this study were 100 respondents. This research focuses on MSMEs in Karawang Regency. This research model uses PLS using SmartPLS 4.0 software. The findings of this study indicate that green human capital, green structural capital, green relational capital and accounting entrepreneurial competence have a significant positive effect on sustainable performance.